Proposal of clipping and inter-modulation noise mitigation method for OFDM signal in non-linear channel - Boonsrimuang, Pisit; Mori, Kazuo; Paungma, Tawil; Kobayashi, Hideo (My University, 2005)
One of the disadvantages of using OFDM is the larger peak to averaged power ratio (PAPR) of the time domain signal as compared with the conventional single carrier transmission method. The OFDM signal with larger PAPR will cause the undesirable spectrum regrowth and the larger degradation of bit error rate (BER) performance both due to the inter-modulation products occurring in the non-linear amplifier at the transmitter. The clipping method in conjunction with the Decision Aided Reconstruction (DAR) method is well known as one of the solutions to improve the BER performance with keeping the better PAPR performance. However, the DAR method is proposed to mitigate only the clipping noise and not for the inter-modulation noise. In this paper, we propose the Improved DAR (IDAR) method, which can mitigate both the clipping noise and inter-modulation noise on the basis of DAR method. The proposed method enables the efficient usage of transmission power amplifier at the transmitter with keeping the better PAPR and BER performances. This paper presents various computer simulation results to verify the performance of proposed IDAR method in the non-linear channel. Copyright © 2005 The Institute of Electronics, Information and Communication Engineers.
Keywords: Clipping; DAR; IDAR; Non-linear channel; OFDM; PAPR